Understanding strategic alliance life cycle: A 30 year literature review of leading management journals - Mayank Dhaundiyal; Joseph Coughlan (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This paper contributes to the strategic alliance literature by undertaking a literature review of the burgeoning strategic alliance literature published in the last three decades in the mainstream management journals to fulfil two primary objectives. First, to bring a coherent structure into the fairly vast and growing alliance literature and second, to serve as a medium for a holistic understanding of the major life stages of strategic alliances. This is done by first dividing the alliance literature into three distinct yet related alliance life stages namely the pre-alliance stage, alliance formation stage and the alliance management and performance stage, and then by discussing in detail the three alliance stages individually. The paper would be useful for academics as well as practitioners looking to get a holistic understanding of strategic alliances and its three distinct yet related life stages and the key research papers which have been published focussing on each of these alliance stages.
Keywords: L14; L24; 650; strategic alliances; literature review; interorganizational relationships; interfirm partnerships; joint ventures